Whose Cost of Living? - Prais, S. J. (Review of Economic Studies, 1959)
Journal Article Whose Cost of Living? Get access S. J. Prais S. J. Prais London and Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 26, Issue 2, February 1959, Pages 126–134, https://doi.org/10.2307/2296170 Published: 01 February 1959